The unfree professions : German lawyers, teachers, and engineers, 1900-1950 - Jarausch, Konrad Hugo (Oxford University Press, 1990)
How could educated professionals have supported the Nazi movement and collaborated with Hitler's inhuman policies? Jarausch examines this fascinating and largely unexplored subject, tracing the social, ideological, and political development of three representative German professions--law, teaching, and engineering--from the late Empire to the early Federal Republic. Based on a reformulated professionalization theory and on authoritative statistics, he describes professional prosperity and prestige in the Second Reich and analyzes the social crisis brought on by hyperinflation, stabilization, a.